Dampak Kecanduan Game Online Terhadap Penilaian Hasil Belajar Siswa di SMP Al Mazaya Islamic Banjarmasin - Rizky Januar Wahab (INDONESIAN COUNSELING AND PSYCHOLOGY, 2022)
Guidance and Counseling at this school, students who are addicted to online games have low learning outcomes. The low learning outcomes are also caused because the child pays less attention during the ongoing learning process in the classroom because of his laziness and the child does not do the assignments given by the subject teacher because friends invite him to play online games. This research is a qualitative research using data collection methods in the form of interviews and documentation. This research is a narrative in nature which produces descriptive data in the form of speech, writing, so as to systematically produce facts about the actual state of the object and pressure on the basic facts that occur at SMP Al Mazaya Islam Banjarmasin. Based on the results of data analysis that was carried out at SMP Al Mazaya Islamic Banjarmasin entitled "The Impact of Online Game Addiction on Assessment of Student Learning Outcomes at SMP Al Mazaya Islamic Banjarmasin, several things can be interpreted as follows: Factors of online game addiction in students at SMP Al Mazaya Islamic Banjarmasin is a feeling of laziness in doing schoolwork, inviting friends to play online games and lack of supervision from parents. The impact of online game addiction on the assessment of student learning outcomes at SMP Al Mazaya Islamic Banjarmasin is a decrease in report cards, disrupted learning concentration and lazy to follow learning.